Hubungan Mutu Pelayanan Kesehatan dengan Kepuasan Pasien Poli Umum di Puskesmas Baiturrahman Banda Aceh - Syarifah Fazhila Azzahra; Tahara Dilla Santi; Nopa Arlianti (Pelantar Press, 2025)
Patient satisfaction is a level of feeling that arises as a result of the performance of health services obtained after the patient compares. The aim of this research is to determine the relationship between the quality of health services and the satisfaction of general polypatients at the Baiturrahman Community Health Center in Banda Aceh. This research contains descriptive analytics with a cross sectional design. The population in this study were patients who came to the Baiturrahman Community Health Center general clinic from January to December 2023, totaling 368 people, with a sample of 80 people and taken using accidental sampling technique, the research was conducted on January 22-31 2024 by means of interviews and questionnaires. Data were analyzed using the chi-square test. the results show that there is a relationship between patient satisfaction and responsiveness (p-value 0.019), physical evidence (p-value 0.024), and guarantee (p-value 0.0014), while what is not related to patient satisfaction is reliability (p-value 0.594). empathy (p-value 0.717)